O Corpo e o Verbo: Interferências nas Relações de Afeto, em Lavoura Arcaica de Raduan Nassar - Paula, Marcela Magalhães de (2008)
This study examines how the body and the verb interfere in family relationships, in the book Lavoura arcaica of writer Raduan Nassar. Thus, we observed the context affective of family, addressing issues of fundamental concepts of the novel, such as eroticism, the desire, the metalanguage and ambiguity, running the behavior of characters in the book in question. Analizes also as the body is a topic of tension, since the beginning of human history, and how it is in the nassarian work. In consequence, some theoretical studies are listed on the topic liked within the sphere of construction of affection, such also in areas like sexual division of gender. We studied how the magnitude of eroticism and the body contaminated the language of André, through a position that, for us, to fold freedom against authoritarianism and the word "false" the father. Among various possibilities for reading, we established a rapprochement between the conceptualization of the libertine, defined by several authors, to begin an analysis that will address the proposals between the poetic and own eroticism. Also emphasizes the ambiguity as one of the most striking features of reaffirmation of the protagonist as subject. The dubiety of André skepticism show up as stage where the character sets and provides their strategies of using the body to deal with a speech libertarian against exclusion, alienation, the order and authoritarianism.